Arbitration in Asia: What does the future hold? - Godwin, Peter (Journal of Malaysian and Comparative Law, 2017)
International arbitration is now widely accepted in Asia as the preferred form of dispute resolution in cross border transactions. Gone (mainly) are the days when arbitration was seen as a new process of which clients should be suspicious.